Research on the scatter features of the PKiKP/PcP amplitude ratio and the inner core boundary density contrasts beneath Northeast Asia - Zhang, Haodong; Ai, Yinshuang; He, Yumei (Science China. Earth sciences, 2021)
Quantifying the density contrasts of the Earth’s inner core boundary (ICB) is crucial to understand core-mantle coupling and the generation of the geodynamo. The PKiKP/PcP amplitude ratio is commonly used to obtain the density contrast at the ICB, but its applications are limited by scattered observed data. In this study, we selected the PKiKP and PcP phases reflected at the same region of inner-core and core-mantle boundaries beneath Northeast Asia from different earthquakes for the first time, and the observations suggested that the PKiKP/PcP amplitude ratio is widely scattered. We also compared the PKiKP and PcP amplitudes, which demonstrated that the scatter cannot be attributed only to ICB anomalies but might also arise from raypath differences and heterogeneities throughout the crust and mantle. By fitting the observed PKiKP/PcP amplitude ratio, we obtained a density contrast of approximately 0.65 g cm −3 and a compressional velocity contrast of approximately 0.87 km s −1 at the ICB beneath Northeast Asia. The larger contrast values indicate the possible occurrence of local crystallization occurring at the inner core surface.